IMPLEMENTASI METODE RECIPROCAL TEACHING BERBASIS KECAKAPAN BERPIKIR KRITIS DALAM MENINGKATKAN PEMAHAMAN KONSEP AKIDAH AKHLAK - Tri Marissa Hiza; Baharudin Baharudin; Agus Susanti (TEACHING : Jurnal Inovasi Keguruan dan Ilmu Pendidikan, 2026)
Learning Akidah Akhlak has an important role in shaping students' understanding of faith and moral behavior, but in practice the learning process is still often dominated by conventional methods centered on teachers so that student involvement and critical thinking skills have not developed optimally. This study aims to determine the implementation of the reciprocal teaching learning method based on critical thinking skills in improving students' understanding of the concept of Moral Faith. This study uses a qualitative approach with a descriptive type of research. Data collection techniques are carried out through observation, interviews, and documentation, then analyzed through the stages of data reduction, data presentation, and conclusion drawn. The results of the study show that the reciprocal teaching learning method is applied through four main stages, namely predicting, questioning, clarifying, and summarizing which encourage students to discuss, ask, and re-explain the material learned. Although the level of student activity is still relatively low, this method shows the potential in helping students understand the concept of Moral Faith through discussion activities, explaining material to each other, and clarifying understanding between students. Thus, the reciprocal teaching learning method can be an alternative learning strategy that supports improving students' understanding of concepts and critical thinking skills.